Back Cover: Plasma Process. Polym. 5∕2015. Issue 5 (May 2015) - Solař, Pavel; Kylián, Ondřej; Petr, Martin; Hanuš, Jan; Choukourov, Andrei; Slavínská, Danka; Biederman, Hynek
<x xml:space="preserve">Abstract</x> Back Cover: The growth of columnar silver films was enhanced by deposition over C:H plasma polymer nanoparticles. This enables to prepare columnar structures growing from the particle seeds. The silver was sputtered over the nanoparticles in perpendicular direction and at different angles ranging from 40 to 80°. As an example silver GLAD deposited over C:H nanoparticles at angles 40 and 70° is shown. Further details can be found in the article by Pavel Solař et. al. on page 486.